Predictive Value of Free Triiodothyronine to Free Thyroxine Ratio in Euthyroid Patients With Myocardial Infarction With Nonobstructive Coronary Arteries - Gao, Side; Ma, Wenjian; Huang, Sizhuang; Lin, Xuze; Yu, Mengyue (Frontiers in Endocrinology, 2021)
Background: Thyroid function is closely involved in cardiovascular diseases. The free triiodothyronine (fT3) to free thyroxine (fT4) ratio has been reported as a risk factor for coronary artery disease, but its prognostic value in euthyroid patients with myocardial infarction with nonobstructive coronary arteries (MINOCA) remains unclear. Methods: A total of 1162 euthyroid patients with MINOCA were enrolled and divided according to decreased tertiles of fT3/fT4 ratio. The study endpoint was major adverse cardiovascular events (MACE), including all-cause death, nonfatal MI, nonfatal stroke, revascularization, and hospitalization for unstable angina or heart failure. Kaplan-Meier, Cox regression, and receiver-operating characteristic analyses were performed. Results: Patients with lower fT3/fT4 tertile levels had a significantly higher incidence of MACE (10.0%, 13.9%, 18.2%; p=0.005) over the median follow-up of 41.7 months. The risk of MACE increased with the decreasing fT3/fT4 tertiles even after multivariate adjustment (tertile1 as reference, tertile2: HR 1.58, 95% CI: 1.05-2.39, p=0.030; tertile3: HR 2.06, 95% CI: 1.17-3.11, p=0.006). Lower level of fT3/fT4 ratio remained a robust predictor of MACE in overall (HR 1.64, 95% CI: 1.18-2.29, p=0.003) and in subgroups. When adding fT3/fT4 ratio [area under the curve (AUC) 0.61] into the thrombolysis in myocardial infarction (TIMI) risk score (AUC 0.69), the combined model (AUC 0.74) yielded a significant improvement in discrimination for MACE (ΔAUC 0.05, p=0.023). Conclusions: Low level of fT3/fT4 ratio was strongly associated with a poor prognosis in euthyroid patients with MINOCA. Routine assessment of fT3/fT4 ratio may facilitate risk stratification in this specific population.